Hsa-miR-99b/let-7e/miR-125a Cluster Regulates Pathogen Recognition Receptor-Stimulated Suppressive Antigen-Presenting Cells - Hildebrand, Dagmar; Eberle, Mariel-Esther; Wölfle, Sabine Marie; Egler, Franziska; Sahin, Delal; Sähr, Aline; Bode, Konrad A.; Heeg, Klaus (Frontiers in Immunology, 2018)
Antigen presenting cells (APCs) regulate the balance of our immune response towards microbes. Whereas immunogenic APCs boost inflammation and activate lymphocytes, the highly plastic cells can switch into a tolerogenic/suppressive phenotype that dampens and resolves the response. Thereby the initially mediated inflammation seems to prime the switch of APCs while the strength of activation determines the grade of the suppressive phenotype. Recently we showed that pathogen recognition receptor-mediated pro-inflammatory cytokines reprogram differentiating human blood monocytes in vitro towards an immunosuppressive phenotype through prolonged activation of signal transducer and activator of transcription (STAT) 3. The TLR7/8 ligand R848 (Resiquimod) triggers the high release of cytokines from GM-CSF/IL-4-treated monocytes. These cytokines subsequently upregulate T cell suppressive factors, such as Programmed death-ligand 1 (PD-L1) and Indolamin-2,3-Dioxygenase (IDO) through cytokine receptor-mediated STAT3 activation. Here we reveal an essential role for the micro-RNA (miR) hsa-miR-99b/let-7e/miR-125a cluster in stabilizing the suppresive phenotype of R848-stimulated APCs on different levels. On the one hand the miR cluster boosts R848-stimulated cytokine production through regulation of MAPkinase inhibitor Tribbles homolog 2 (TRIB2), thereby enhancing cytokine-stimulated activation of STAT3. One the other hand, the STAT3 inhibitor suppressor of cytokine signaling-1 (SOCS1) is targeted by the miR cluster, stabilizing the STAT3-induced expression of immunosuppressive factors PD-L1 and IDO. Finally hsa-miR-99b/let-7e/miR-125a cluster regulates generation of the suppressive tryptophan (Trp) metabolite kynurenine by targeting the tryptophanyl-tRNA synthetase WARS, the direct competitor of IDO in terms of availability of Trp. In summary, our results reveal the hsa-miR99b/let-7e/miR-125a cluster as an important player in the concerted combination of mechanisms that stabilizes STAT3 activity and thus regulate R848-stimulated suppressive APCs.